Effect of biochar and inorganic fertilizer on the quality of beetroot (Beta vulgaris L.) in Kenya - Kwizera, E.; Mungai, N. W.; Opiyo, A. M.; Niyokuri, N. A. (International Journal of Horticultural Science, 2024)
Despite its health benefits, the production and quality of beetroot is still low in Kenya due to the application of non-recommended rates of fertiliser and soil amendment. This research aimed at contributing to the improvement of the beetroot quality in Kenya. It was designed to determine the effects of biochar and NPK (17-17-17) on the quality of beetroot in Kenya. An RCBD factorial experiment was conducted at Egerton University farm, Kenya, for two seasons. Biochar (0, 5, 10 t/ha) and NPK (0, 200, 300 and 400 kg/ha) were applied together before planting. Data were collected on beetroot diameter, total phenolics, total soluble solids, calcium, iron and phosphorus contents and analysed using SAS statistical software. The co-application of biochar and NPK significantly (p≤0.05) increased the beetroot diameter, iron, calcium, phosphorus, TSS and phenolics content in season two and not in season one. The sole application of biochar showed a significant increase in the iron content of beetroot in season one. However, biochar did not have a significant effect on beetroot diameter, mineral content, TSS and phenolics content of beetroot in season two. The sole application of NPK at 200, 300 and 400 kg/ha significantly (p≤0.05) increased the diameter of beetroot and iron content in both seasons one and two and also significantly improved the calcium and phosphorus content in season two. These NPK levels were not statistically different from each other, but different from the control. It is therefore recommended to apply NPK and biochar for quality beetroot.